English grammar a university course - Downing, Angela (Routledge, Taylor & Francis Group, 2015)
This comprehensive reference and practice grammar is designed for advanced students of English as a foreign language. It takes language functions as its basis and explores these in terms of the language units that realize them. Form is related to meaning which in turn is related to situation.